FAKTOR KEUANGAN PADA PENGUNGKAPAN WAJIB - Christina Verawati Situmorang; Arthur Simanjuntak (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this study is to test financial ratios (leverage ratios, profitability ratios and liquidity ratios) to mandatory disclosure (study of State-Owned Companies listed on the IDX in 2019 – 2021). This type of causal associative research with data collection techniques in the form of documentation. This study uses secondary data and research methods using descriptive statistical analysis, classical assumption test, regression test and hypothesis testing. The number of samples is 19 state-owned companies listed on the IDX with 3 years of observation, bringing a total of 57 observations. Data obtained from the website of the Indonesia Stock Exchange (www.idx.co.id). The data analyzed in this study were processed from the financial reports and annual reports of related companies. The results of this study indicate that the leverage ratio and liquidity ratio have a significant negative effect on mandatory disclosure, while the profitability ratio has a significant positive effect on mandatory disclosure. Simultaneously leverage ratios, profitability ratios and liquidity ratios have a positive and significant effect on mandatory disclosure. The difference between this study and other studies is that this study focuses on financial ratios, namely the leverage ratio with the debt to total assets indicator, the profitability ratio with the return on assets indicator and the liquidity ratio with the current ratio indicator on mandatory disclosure. This research was conducted at State-Owned Enterprises for the 2019-2021 period.